Temporal Misrecognition - Katharina Wolf (The Journal of Public Interest Communications, 2026)
Environmental governance decisions are inherently communicative, shaping how risks, responsibilities and public interests are defined and justified. This paper examines how future generations are recognized within environmental governance, using Western Australia as an empirical case. Drawing on recognition theory, climate ethics and public interest communications scholarship, it conceptualizes their exclusion as temporal misrecognition: acknowledgement without meaningful standing in decision-making. Analysis of Environmental Protection Authority reports and Office of the Appeals Convenor decisions from 2021 to 2025 finds that intergenerational equity and sustainability are routinely invoked but rarely carry substantive weight. The paper argues that public interest must be understood temporally and considers how future-oriented institutional mechanisms might make long-term impacts more visible, contestable and accountable.